Family physicians as advocates for primary health care in Botswana - Billy M. Tsima; Yaone Bogatsu; Keneilwe Motlhatlhedi; Claire Brockbank; Sunanda C. Ray (African Journal of Primary Health Care & Family Medicine)
Advocacy for family medicine in Botswana has been facilitated by good cooperation between the University of Botswana (UB), the Botswana Association of Family Physicians and the Botswana Health Professions Council. The importance of family physician leadership in putting primary health care (PHC) at the centre of the health system has been recognised and acted on by the Ministry of Health. Family medicine teaching is integrated throughout the 5-year undergraduate medical curriculum at the UB Faculty of Medicine and takes place in rural and urban training complexes. Family medicine is a popular career choice but developing a critical mass of family physicians is limited by the low number of training posts available each year. Botswana has a strong PHC foundation with village health committees, village development committees and community home-based care teams, led by district health management teams (DHMTs). There are not enough family physicians currently in the public sector to provide sufficient clinical leadership for the DHMTs as well as to provide clinical supervision of medical officers and nursing staff in clinics, and primary and district hospitals, as well to be actively involved in advocacy for health equity and quality of care to policymakers. Active participation in regional initiatives to expand family physician training opportunities could contribute to strengthening the health workforce in Botswana.